Strength and Serviceability of Hanger Connections - Thornton, William A. (Engineering Journal, 1992)
Hanger connections involve bolts in tension due to direct loads and prying action and bending of tee flanges or angle legs. It is the purpose of this paper to show that the analysis method of the latest AISC Manuals, both ASD and LRFD versions, can with minor modification allow for a greatly increased design strength and a more reliable prediction of serviceability loads. The strength of hanger connections is due mainly to the strength of the bolts but is affected by the bending of the hanger flanges which induces prying action in the bolts. Previous emphasis on this problem has focused on the determination of the actual prying force Q rather than the overall behavior of the connection itself. This paper concentrates on assessing the strength of the connection, both ultimate strength and yield (or separation) strength.